Взаимозаменяемость в машиностроении и приборостроении - Якушев А. И. Александр Иванович; Валединский А. С. Алексей Сергеевич; Воробьев Ю. А. Юрий Александрович; Калитенко В. Г. Вячеслав Григорьевич; Тищенко О. Ф. Олег Федорович (Библиотека по стандартизации Кн. 1)
Исключено из фонда НТБ ТПУ